Synthesis and properties of bis-corannulenes - Halilovic, Dzeneta (2022)
Corannulenecarbaldehyde and corannulenylmethyl triphenylphosphonium bromide are combined through the Wittig olefination reaction to furnish dicorannulenylethene with 70% yield. A subsequent oxidative photocyclization leads to annulation of the corannulene nuclei to produce a C42H18 nanographene structure in 59% yield. Interestingly, only the trans isomer of the dicorannulenylethene forms cocrystals with fullerene C60 through concave-convex and convex-convex π-π stacking interactions. The Mallory photocyclization could be extended to a phenanthrene-based diarylethene precursor to yield a large bicorannulene system.